A plant perspective on nitrogen cycling in the rhizosphere. (2nd March 2019) - Moreau, Delphine; Bardgett, Richard D.; Finlay, Roger D.; Jones, David L.; Philippot, Laurent
Abstract: Nitrogen is the major nutrient limiting plant growth in terrestrial ecosystems, and the transformation of inert nitrogen to forms that can be assimilated by plants is mediated by soil micro‐organisms. The last decade has witnessed many significant advances in our understanding of plant–microbe interactions with evidence that plants have evolved multiple strategies to cope with nitrogen limitation by shaping and recruiting nitrogen‐cycling microbial communities. However, most studies have typically focused on the impact of plants on only one, or relatively few, processes within the nitrogen cycle. This review synthesizes recent advances in our understanding of the various routes by which plants influence the availability of nitrogen via an array of interactions with different guilds of nitrogen‐cycling micro‐organisms. We also propose a plant trait‐based framework for linking plant nitrogen acquisition strategies to the activities of nitrogen‐cycling microbial guilds. In doing so, we provide a more comprehensive picture of the ecological relationships between plants and nitrogen‐cycling micro‐organisms in terrestrial ecosystems. Finally, we identify previously overlooked processes within the nitrogen cycle that could be targeted in future research and be of interest for plant health or for improving plant nitrogen acquisition, while minimizing nitrogen inputs and losses in sustainable agricultural systems. Aplain language summary is available for this article. Abstract : Plain Language Summary